PERTANGGUNGJAWABAN PIDANA PELAKU SODOMI TERHADAP KORBAN YANG TELAH CUKUP UMUR - Farry Indra Prawira, I Nyoman; Markeling, I Ketut (Kertha Wicara : Journal Ilmu Hukum, 2014)
The title of this paper is “Criminal Responsibility of Sodomy Perpetrators against Adult Victim”. The Issues to be discussed is a regulation of sodomy in accordance with the laws and Regulation in Indonesia and the criminal responsibility of the sodomy perpetrators against adult victims. The research method of this paper is normative research method cause of void of legal norms on article 292 Indonesian Code Penal. Regulation of Indecent act of homosexual on article 292 Indonesian Code Penal and article 82 Laws and Regulation Number 23 Year 2002 concerning to Child Protection but the Regulation limited that victims are children. The term of sodomy is not specifically regulated in the laws and regulations in Indonesia. The perpetrators of sodomy which victims are adult to be accounted for and charged under Article 290 actions of the Indonesia Penal Code with a maximum penalty of seven years imprisonment cause it met the formulation of it article. So the conclusion of this paper is sodomy is not yet regulated on Indonesia Laws and Regulation but it can prosecute criminal responsibility perpetrators of sodomy which is the victim is adults.
Keywords: Criminal Responsibility, Perpetrators, Sodomy, Adult Victims